IDENTIFIKASI BAHAYA ERGONOMI TERHADAP BEBAN KERJA PADA PEKERJA DI INDUSTRI PABRIK TAHU DELI - Anggun Adi Syafila; Susilawati (CV. ADIBA AISHA AMIRA, 2024)
The manufacturing industry manages the raw materials produced into products that can be consumed by humans. In Indonesia, industrial development is currently growing rapidly, not only in large industries but also in small industries. One small industry that is currently popping up a lot is the tofu industry. The industry is required to improve the quality of the products it produces in order to meet consumer demand. The higher the productivity, the greater the risk of work hazards arising. The purpose of this research is to identify ergonomic hazards that occur in tofu industry workers. This research method uses a qualitative method which obtained information from a worker informant and a literature review study method by taking the topic as a study accessed on the Google Scholar database. The results of the study stated that there is a risk of ergonomic hazards that occur in tofu industry workers. The conclusion is that there is an ergonomic hazard to the workload caused to the tofu deli industry workers.